2021
DOI: 10.35290/rcui.v8n1e.2021.501
|View full text |Cite
|
Sign up to set email alerts
|

Aprendizaje B-learning como enfoque mezclado no agitado con las teorías del aprendizaje

Abstract: La evolución que se ha suscitado en los diferentes ámbitos (económicos, políticos, tecnológicos, sociales, educativos, religiosos, entre otros) de la humanidad, ha despertado especial interés en la implementación innovadora de sistemas educativos, sustentados en la evolución y practicidad que promueven las tecnologías de la información y comunicación (TIC), con miras a generar cambios drásticos que surgen de los diferentes elementos del acto didáctico. El objetivo del estudio, es interpretar la importancia de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Continuing with all the theories related to ICT (Pirnau et al,2020), (Farias-Gaytán et al,2023), (Becerra et al,2022), and (Arellano Espinoza et al,2021), in the educational field, we can mention that the importance of the use of ICT by professors emphasizing on boosting the preparation of interactive digital competences (Castellanos et al,2019) in higher education institutions, show the urgency of the needs while using ICT (Althibyani et al,2023), besides the contents on theory that are taught due to they need an interaction and complementation with enough practice and collaborative learning, so the use of ICT is required (Makananise et al,2023),several researchers found that not enough value is given to the functional particularities of ICT (Palacios-Núñez et al,2022), in the educational processes carried out in these centers, representing a current problem not yet solved, therefore it can be evidenced that technological innovations have still not taken the place they need in the educational context, despite the fact that it is clear the transcendence in the changes of academic processes, based on the imminent requirements of the use of ICT (Domingo-Coscollola et al,2020). Internationally, there is a model of ICT policies that is worked by the different governments from all the countries, each one has established the ways of working according to the subject, in Peru (Rivera et al,2020), the government announced the policies of digital transformation throughout the country, a process that has been progressing gradually.…”
Section: Introductionmentioning
confidence: 86%
“…Continuing with all the theories related to ICT (Pirnau et al,2020), (Farias-Gaytán et al,2023), (Becerra et al,2022), and (Arellano Espinoza et al,2021), in the educational field, we can mention that the importance of the use of ICT by professors emphasizing on boosting the preparation of interactive digital competences (Castellanos et al,2019) in higher education institutions, show the urgency of the needs while using ICT (Althibyani et al,2023), besides the contents on theory that are taught due to they need an interaction and complementation with enough practice and collaborative learning, so the use of ICT is required (Makananise et al,2023),several researchers found that not enough value is given to the functional particularities of ICT (Palacios-Núñez et al,2022), in the educational processes carried out in these centers, representing a current problem not yet solved, therefore it can be evidenced that technological innovations have still not taken the place they need in the educational context, despite the fact that it is clear the transcendence in the changes of academic processes, based on the imminent requirements of the use of ICT (Domingo-Coscollola et al,2020). Internationally, there is a model of ICT policies that is worked by the different governments from all the countries, each one has established the ways of working according to the subject, in Peru (Rivera et al,2020), the government announced the policies of digital transformation throughout the country, a process that has been progressing gradually.…”
Section: Introductionmentioning
confidence: 86%
“…En los procesos educativos, sin importar la modalidad que se trate, se suscita que contribuyen al fortalecimiento de las relaciones interpersonales entre estudiantes, y estos con el docente; esta interacción adquiere importancia para el logro de los objetivos didácticos, siendo la creatividad del docente la que determine el empleo de estrategias didácticas; de este modo, se puede generar interacción en lo virtual mediante la plataforma educativa, los foros de discusión, chat, correo electrónico, entre otros; mientras que en lo presencial, se realiza mediante el trabajo en equipo, debates, lluvia de ideas u otras técnicas que promueven el intercambio de opiniones (Arellano et al, 2021).…”
Section: Caracterización Del B-learningunclassified